Oxygen free radicals and congestive heart failure. Issue 5 (May 1991) - Belch, J J; Bridges, A B; Scott, N; Chopra, M
Abstract : Plasma lipid peroxides (malondialdehyde) and thiols were measured in 45 patients with congestive heart failure and 45 controls. Malondialdehyde concentrations were significantly higher in the patients with congestive heart failure (median 9.0 nmol/ml interquartile range (IQR) 7.9-10.2) than in the controls (median 7.7 nmol/ml (IQR 6.9-9.2)). Plasma thiols were significantly lower in congestive heart failure (median 420 mumol/l (IQR 379-480)) than in the controls (median 463 mumol/l (IQR 445-525)). There was a significant but weak negative correlation between malondialdehyde and left ventricular ejection fraction (r = -0.35) and a positive correlation between plasma thiols and left ventricular ejection fraction (r = 0.39). This study provides clinical support for experimental data indicating that free radicals may be important in heart failure. It also suggests that the degree of free radical production may be linked to the severity of the disease.